Islamic Adaptive Resilience in Post-Conflict Schools and Natural Disasters of Aceh: A Longitudinal Case Study - Bashori, Khoiruddin; Moerdijat, Rara Lestari (International Journal of Islamic Educational Psychology, 2023)
Adaptive resilience, as a theory, is examined from an Islamic perspective in schools that practice the Dayah system in Aceh. This study aims to identify Islamic adaptive resilience in schools that were built after conflicts and natural disasters. The method used in this study is qualitative, employing a case study approach. Data was collected through observation, interviews, and documentation at three schools in Aceh and their foundations in Jakarta. Data analysis was conducted using NVivo. The results demonstrate that Islamic adaptive resilience plays an active role in the post-disaster and post-conflict school recovery processes. The common aspects of Islamic adaptive resilience that were found include learning from experience, strong leadership at both the top and middle levels, collaboration, staff engagement, and well-being. The research recommends that institutions prioritize flexibility and the ability to respond quickly to any problem, as well as a commitment, particularly from the leadership, to the vision and mission that were established from the outset. Building a school with a strong foundation in beliefs and incorporating local culture requires significant attention in order to maintain and operate a creative and harmonious organization. This research contributes to assisting schools in post-conflict and post-disaster areas in developing effective strategies to promote adaptive resilience and enhance their ability to respond to future challenges. Moreover, it may contribute to the broader literature on leadership, organizational resilience, and Islamic values, providing insights into how leaders can integrate Islamic values into their leadership practices to promote organizational resilience in various context.